2021
DOI: 10.3390/su13063558
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbonization Process on the Mechanical Properties of Nano-MgO Modified Cement Soil

Abstract: In order to explore the modification effect of carbonization time on nano-MgO-modified cement soil, unconfined compressive strength tests of nano-MgO-modified cement soil with carbonization times of 0 h, 6 h, 1 d, 2 d and 4 d were carried out. A method for normalizing the stress–strain curve was proposed, and the influence of nano-MgO content and carbonization time was investigated from the three aspects of compressive strength, peak strain and energy dissipation. The test results show the following: (1) The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Furthermore, the fair fitting results also suggested that the ε frelation of NM-treated loess was not sensitive to NM and curing, which brought conv ience in engineering application. Figure 10 exhibits the data of nano-SiO 2 (NS)-and nano-MgO (NM)-treated clays extracted from the literature [22,31,37,53]. Twelve pairs of ε f and q u were fitted according to Equation ( 2), and the fitting results are exhibited in this figure.…”
Section: Strain At Failurementioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the fair fitting results also suggested that the ε frelation of NM-treated loess was not sensitive to NM and curing, which brought conv ience in engineering application. Figure 10 exhibits the data of nano-SiO 2 (NS)-and nano-MgO (NM)-treated clays extracted from the literature [22,31,37,53]. Twelve pairs of ε f and q u were fitted according to Equation ( 2), and the fitting results are exhibited in this figure.…”
Section: Strain At Failurementioning
confidence: 99%
“…It demonstrated that the 50 E of NM-treated loess was proportiona to u q , but in a nonzero-intercept way. Therefore, their relationship could be described as Figure 13 presents the E 50 -q u relationships of nanomaterial-stabilized clays extracted from literature [22,31,37,53]. Based on Equation (3), information about the parameters η and β could be obtained together with the determination coefficient R 2 : (1) For the NS (0~4%) stabilized clay with E 50 of 3~38 MPa and q u of 0.4~2.1 MPa, the fitting parameter η and β were 54.1 and −10.83, respectively; (2) For the clay treated with NS (0~1%) and polyester fiber (PF) (0~0.5%), the η and β were considered to be 16.4 and −3.1473, respectively;…”
Section: Deformation Modulusmentioning
confidence: 99%
See 3 more Smart Citations